CHILDREN’S STORIES OF ANVAR MAMMADKHANLI: COLLECTION OF MORAL AND SPIRITUAL VALUES - Mammadova Shohrat (International Journal of Innovative Technologies in Social Science, 2024)
The general picture of the literary and cultural process in the middle of the last century is connected to the dynamic searches in children’s literature in one direction. Rooting of prose, poetry, dramaturgy, publicism, as well as literary-theoretical thought to the national thought is charged with reality in its entirety and actualizes society’s consideration of ethnographic and historical richness as a side. Khanimana Alibayli, Teymur Elchin, Ali Karim, Tofig Mutallibov, Ilyas Tapdig, Hikmet Ziya, Mastan Guler, Fikret Sadiq, Mammad Aslan, Zahid Khalil, Tofig Mahmud in poetry, Khalida Hasilova, Alaviya Babayeva, Nariman Suleymanov, Aziza Ahmadova, Ali Samadov and prose. etc. such talented artists contributed to children’s literature with their rich literary thought. Anvar Mammadkhani is also in this rank with his high creative intellect and is one of the writers who have done necessary work in the matter of transmitting ethnocultural culture as a potential. "Qızıl qönçələr", "Buz heykəl", "Baş xiyabanda", "Anamın çırağı", "Sevinc", "O mahnılarda qayıtdı", "Əfsanəvi dağlar" and others. is of exceptional importance in the formation of children at the level of national and moral values. The harsh realities of life and the methods of presentation from folklore, the detail revealed by the textual information have been realized at different levels as a life story in the writer’s mind at all times. A. Mammadkhanli’s observations, as well as the colorful aspects that he lived and observed in terms of the vicissitudes of the environment and time, the story, story-tale, story-narrative, etc. has become a topic in its context. The internal and inter-situation of situations and its presentation in the context of events and stories with its high creative intelligence have an exceptional function in the formation of children in terms of national and moral values.